Shaking table tests on a high-rise RC building model having torsional eccentricity in soft lower storeys. - Ko, Dong-Woo
A series of shaking table tests on a 1:12-scale model using scaled TaftN21E earthquake records were conducted to investigate the seismic performance of a 17-storey high-rise reinforced concrete structure with a high degree of torsional eccentricity and soft-storey irregularities in the bottom two storeys. Based on the analysis of test results, the following conclusions were drawn: (1) the model responded mainly in the coupled mode of translation and torsion or in the torsional mode. Under severe table shaking, the flexible side underwent large inelastic deformation, and the predominant mode of the model changed from the coupled mode to the torsional mode, resulting in greatly increased torsional stiffness, thereby limiting damage in the flexible frame; (2) the shear force and deformation of the flexible side were governed by the torsional behaviour, whereas those of the stiff side were affected mainly by the overturning deformation. The lateral stiffness of the shear wall in the torsional mode was about four times that in the coupled mode because the warping deformation due to torsion counteracted the flexural deformation due to overturning moment in the torsional mode; and (3) the reversed cyclic overturning moments predicted by linear elastic dynamic analysis in the direction transverse to the table excitations contradicted unilateral overturning moments of the serviceability-level test results, which showed a bias towards tension or compression in the columns.
Keywords: Reinforced concrete; Shaking table tests; Irregularity; Overturning moment; Torsion